Studies on elemental composition and antioxidant capacity in callus cultures and native plants of Vaccinium myrtillus L. local populations - Veres Bolda, Vanda; Veres Bolda, Vanda (Acta Biologica Szegediensis, 2011)
The biological and medical effects of bilberry fruit (Vaccinium myrtillus L.) are mainly due to high anthocyanin content of tissues. Calli containing anthocyanins, derived from bilberry plants, may represent a potential source of natural colouring matter, pharmaceutical and natural antioxidants. In the present study we investigated the occurrence of differences in elemental composition and antioxidant capacity of the three local populations of mountain bilberry collected in the western region of Romania (Arieseni, Retezat and Sebes Valley) in order to compare the anthocyanin production of plant and callus tissues originated from various plant populations. It was found that K, Fe and Zn content was higher in calli than in intact plant leaves. The excess of latter two microelements, Fe and Zn can induce oxidative stress, and, as a result of the accumulation of reactive oxygen species, various antioxidant mechanisms. The total antioxidant capacity of callus cultures determined by FRAP method (ferric reducing antioxidant power) could be enhanced as a function of increasing adenine sulphate (AS) concentration in the culture medium and it depended on the origin of mother plants. The leaves of intact plants contained higher amount of total non-protein sulfhydryl groups than calli, and the decrease was especially significant in tissue cultures originated from the Retezat region. In contrast, depending on the AS concentration, the anthocyanin content could increase in callus cultures. The tissues originated from various populations exhibited different AS concentration optimum. This suggests that bilberry callus cultures can be a suitable source of the anthocyanins.